Identification of a Glycine Motif Required for Packing in EmrE, a Multidrug Transporter from Escherichia coli - Elbaz, Yael (American Society for Biochemistry and Molecular Biology, 2008)
Glycine residues may play functional and structural roles in membrane proteins. In this work we studied the role of glycine residues in EmrE, a small multidrug transporter from Escherichia coli. EmrE extrudes various drugs across the plasma membrane in exchange with protons and, as a result, confers resistance against their toxic effects. Each of 12 glycine residues was replaced by site-directed mutagenesis. Four of the 12 glycine residues in EmrE are evolutionary conserved within the small multidrug resistance family of multidrug transporters. Our analysis reveals that only two (Gly-67 and Gly-97) of these four highly conserved residues are essential for transporter activity. Moreover, two glycine positions that are less conserved, Gly-17 and Gly-90, demonstrate also a nil phenotype when substituted. Our present results identifying Gly-17 and Gly-67 as irreplaceable reinforce the importance of previously defined functional clusters. Two essential glycine residues, Gly-90 and Gly-97, form a protein motif in which glycine residues are separated by six other residues (GG7). Upon substitution of glycine in these positions, the protein ability to form dimers is impaired as evaluated by cross-linking and pull-down experiments.